Epicardial adiposity as a predictor of COVID-19 severity in overweight and obese patients - M. A. Druzhilov; T. Yu. Kuznetsova (Российский кардиологический журнал, 2022)
Aim. To evaluate epicardial adiposity (EA), verified on the basis of epicardial adipose tissue (EAT) thickness according to echocardiography, as a possible predictor of the severity of coronavirus disease 2019 (COVID-19) course in overweight and obese patients in a retrospective analysis of data.Material and methods. We analyzed data on 165 patients (age, 45,2±4,7 years; men, 67,9%; body mass index, 31,4±3,5 kg/m2) who received outpatient or inpatient treatment for symptomatic COVID-19 in period from March 2020 to November 2021. Patients with diabetes, stage III-V chronic kidney disease and/ or cardiovascular disease were excluded from the analysis, with the exception of hypertension. EA was verified in the case of EAT thickness ≥4,8 mm for persons aged 35-45 years and ≥5,8 mm for persons 46-55 years old.Results. Patients with EA were characterized by higher hospitalization rates (52,2% vs 9,0%, p<0,01), moderate (56,5% vs 19,7%, p<0,01), high and very high severity (17,4% vs 3,3%, p<0,01) of disease course, lung injury of CT-1, CT-2 and CT-3 (32,6% vs 9,8% (p<0,01), 21,7% vs 7,4% (p<0,05), and 15,2% vs 2,5% (p<0,01), respectively), invasive ventilation (8,7% vs 0,8%, p<0,05) and C-reactive protein >10 mg/l (69,6% vs 21,3%, p<0,01). Predictors of hospitalization for symptomatic COVID-19 according to multivariate logistic regression analysis were age, fasting glycemia, systolic blood pressure, EAT thickness, which was characterized by the highest standardized regression coefficient among other predictors (0,384, p<0,001).Conclusion. EAT thickness may be one of the predictors of COVID-19 severity in overweight and obese patients. Persons with EA in the case of COVID-19 need more careful monitoring and measures to prevent severe course and complications.